Exploring the effects of aerobic and resistance exercise on mood-related symptoms and EEG activity - Yuk, Kihoon; Lim, Jawon; Kim, Sangyun; Kim, Tae Yeon; Moon, Hyo Youl (Frontiers in Human Neuroscience, 2025)
IntroductionAnxiety and depression are psychiatric disorders that have a deleterious effect on human mental health. Meanwhile, various forms of exercise have been demonstrated to have beneficial effects on the reduction of symptoms of anxiety and depression. However, the disparate effects of each exercise on mood symptoms remain to be elucidated. This research examines the different effects of each type of exercise on mood symptoms and electroencephalography (EEG) activity.MethodsAccordingly, subjects engaged in six weeks of aerobic and resistance exercises with a 3-week washout period between each intervention. The Score of Hospital Anxiety and Depression Scale (HADS) was employed to assess the severity of both anxiety and depression. For the purposes of EEG analysis, we calculated the values of theta/beta ratio (TBR), Higuchi Fractal Dimension (HFD), and frontal alpha asymmetry (FAA).ResultsBoth types of exercise resulted in the alleviation of both anxiety and depression. Notably, aerobic exercise significantly decreased the score of HADS-A (anxiety), while resistance exercise significantly improved HADS-D (depression). In the context of EEG analysis, a significant decrease of TBR in the left frontal region was observed after aerobic exercise.DiscussionTherefore, these findings emphasize the importance of personalized exercise strategies for those suffering from anxiety and depression. Furthermore, further investigation into the impact of exercise on brain wave activities associated with anxiety and depression are needed.